Low back pain and corporal balance of female brazilian selection canoeing flatwater athletes - Carlos Bolli Mota; Clarissa Stefani Teixeira; Luiz Fernando Cuozzo Lemos (Universidade Federal de Santa Catarina, 2010)
Low back pain has been shown to interfere with body stability. In sports, the study of these relationships is important because the bouts may influence the results of training and competitions. High rates of injury to the lumbar region have been reported for elite female canoe paddlers. The objective of this study was to assess the influence of low back pain on body balance in female athletes of the Brazilian flatwater canoe team. Athletes with low back pain (in the last week) were compared to those without pain in the two-leg and single-leg stance, with the eyes open and closed, using an AccuSway Plus force platform (Advanced Mechanical Technology, Inc.). The variables analyzed were the amplitude of the pressure center in the anteroposterior direction (COPap) and medial-lateral direction (COPml). The results showed higher body ins-tability for athletes with low back pain. For COPml, no significant difference between the two groups was observed for only one condition (single-leg stance) (p = 0.901), and for COPap, no significant difference was observed for two conditions (p = 0.414 and p = 0.567), i.e., single-leg stance and eyes closed. In conclusion, low back pain was harmful to body balance in high-level female canoe paddlers.